The impact of temporary agency work on trade union wage setting: A theoretical analysis - Thomas Beissinger; Philipp Baudy (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
Focusing on the cost-reducing motive behind the use of temporary agency employment, this paper aims at providing a better theoretical understanding of the effects of temporary agency work on the wage-setting process, trade unions' rents, firms' profits and employment. It is shown that trade unions may find it optimal to accept lower wages to prevent firms from using temporary agency workers. Hence, the firms' option to use agency workers may affect wage setting also in those firms that only employ regular workers. However, if firms decide to employ agency workers, trade union wage claims will increase for the (remaining) regular workers. An intensive use of temporary agency workers in high-wage firms may therefore be the cause and not the consequence of the high wage level in those firms. Even though we assume monopoly unions that ascribe the highest possible wagesetting power to the unions, the economic rents of trade unions decline because of the firms' option to use temporary agency work, whereas firms' profits may increase.
Keywords: J51; J31; J23; J42; 330; Trade Unions; Temporary Agency Work; Wage-Setting Process; Labour Market Segmentation; Dual Labour Markets